Tumpek Uduh, Kearifan Lokal Bali untuk Meningkatkan Mutu Pendidikan Karakter - I Nyoman Payuyasa (UHN IGB Sugriwa Denpasar, 2017)
Local wisdom is the values that will be strongly attached to society because of this value through a long travel time, as long as the existence of that society. Local wisdom is a way of life for the people. Trust and respect for the meaning of local wisdom is a seriousness. One of them tumpek uduh / pengatag, as the media is also a reminder that people can understand that character education should be given early on. Seeing the culture of society that is very respectful of local wisdom values, then this local wisdom is a facility and a bridge both to realize the value of character education in learners and the wider community. Synchronization between local wisdom and character education values is required. So that the quality of character education is good with the media of local wisdom.